Atypical Endometrial Hyperplasia or Endometrial Cancer in A 65-Year-Old Woman: A Case Report - Trocadero, Lucian; Brezeanu, Dragoș; Boșoteanu, Mădălina; Vodă, Raluca Ioana; Rotar, Vadym; Ionescu, Paris; Brezeanu, Ana-Maria (International Journal of Innovative Research in Medical Science, 2024)
Atypical endometrial hyperplasia is a condition that denotes the presence of precancerous lesions in the endometrial layer of the uterus. This condition is often linked with several risk factors such as early menarche, nulliparity, diabetes, and obesity. Recently, a 65-year-old woman visited Saint Andrew Hospital Constanta with complaints of postmenopausal menstrual bleeding. Upon examination, her uterus was found to be enlarged, similar to the size of a uterus in the fifth month of pregnancy. Additionally, the uterine wall was relatively firm. To diagnose the condition, the patient underwent a curettage procedure based on transvaginal sonography and magnetic resonance imaging results. The pathological findings confirmed the presence of atypical endometrial hyperplasia. Fortunately, the patient was cured after undergoing a total hysterectomy with bilateral adnexectomy. This treatment approach is often recommended for patients with this condition. In conclusion, it is essential to obtain a histo-pathological sample from patients at menopause with suspect intrauterine images that may suggest malignancy. This helps in the early detection and proper management of atypical endometrial hyperplasia.